STRUKTUR VEGETASI HUTAN PERENGET DIPTEROCARPACEAE DI BUKIT NAHUANG, PEGUNUNGAN MULLER, KALIMANTAN TENGAH (Vegetation Structure of Dipterocarpaceae Perenget Forest in Nahuang Hill, Muller Mountain, Central Kalimantan) - Syamsul Hidayat (Media Konservasi, 2007)
Ecological research for inventory of plant and vegetation structure was conducted at Nahuang forest, Muller Mountains, Central Kalimantan. Seven plots of observation of 20 x 50 m2 were established based on the existing altitude. The result show that for tree category Shorea, Vatica, and Dipterocarpus are the dominant taxa while for seedling and sapling Callophyllum, Sterculia, Syzygium, and Gluta are the dominant genera. The density of tree is relatively high i.e. 557/ha whereas the average of bole diameter is low. There are only 7 trees having bole diameter more than 60 cm. This result is important for management authority as a basic knowledge to protect forest from destructive activities.Keywords : Vegetation structure, Dipterocarpaceae forest inventory, Central Kalimantan virgin forest